Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 2 - Nonlinear Functions - 2.4 Exponential Functions - 2.4 Exercises - Page 86: 4



Work Step by Step

The answer is D, because when $x=-1$, $3^{-x}=3^1=3$ so $y=3$. And also when $x=0$, $3^{-x} = 3^0=1$ so $y=1$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.